2014
DOI: 10.1007/s00296-014-3123-y
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of ethnic group and socioeconomic status to degree of disability in rheumatoid arthritis in Chilean patients

Abstract: The aim of this study was to estimate the contributions of ethnic group and socioeconomic status as social determinants related to disability and disease activity in Chilean Mapuche and non-Mapuche patients with rheumatoid arthritis (RA). Descriptive cross-sectional study with a stratified hospital-based sample of 189 patients in treatment with disease-modifying anti-rheumatic drugs. We assessed disability as categorical variable with the Health Assessment Questionnaire, disease activity with the Disease Activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 9 publications
0
15
0
1
Order By: Relevance
“…While several studies in this review reported lower education and income levels in rural settings, most eligible studies did not adjust for socioeconomic status. Those that did (8) were underpowered to examine multivariable relationships. It is therefore difficult to determine, based on existing evidence, whether rurality is an independent predictor of poor outcome in RMD or a surrogate marker for socioeconomic status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While several studies in this review reported lower education and income levels in rural settings, most eligible studies did not adjust for socioeconomic status. Those that did (8) were underpowered to examine multivariable relationships. It is therefore difficult to determine, based on existing evidence, whether rurality is an independent predictor of poor outcome in RMD or a surrogate marker for socioeconomic status.…”
Section: Discussionmentioning
confidence: 99%
“…However, education level and household income was not adjusted for in the analysis. Alarcón et al (8) recruited 189 patients from the rheumatology clinic of a referral center in 1 region of Chile. This center also acted as a referral center for other regions.…”
Section: Significance and Innovationsmentioning
confidence: 99%
“…Finding out causes of disability in patients with RA may facilitate development of measures to preserve independency in these patients. There is a recent trend toward exploring factors underlying disability in patients with RA [1][2][3][4][5][6][7][8][9][10]. Older adults are at a high risk for disability and in ammatory rheumatic disorders such as RA may further increase this risk.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence and severity of rheumatic diseases and musculoskeletal (MSK) disorders may vary according to ethnicity and socioeconomic conditions [ 1 , 2 ]. Genetic and epidemiological studies have indicated that certain rheumatic conditions may have greater prevalence and severity in specific indigenous groups [ 3 ].…”
Section: Introductionmentioning
confidence: 99%